2013
DOI: 10.1111/1467-968x.12029
|View full text |Cite
|
Sign up to set email alerts
|

Synchronic Variation in The Old English Perfect

Abstract: In Old English, the present/past dichotomy of the Germanic verbal system was supplemented by the development of periphrastic forms such as the perfect and pluperfect. However, the inflected past tense continued to be used beside these newer forms to express similar temporal content. The research presented here aims to provide accurate quantitative data on the distribution within Old English texts both of the periphrastic forms and of semantically comparable preterites. Upon analysis, these data reveal a substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…An additional way in which translation can influence the form of texts was suggested by Macleod (: 333–6), which found that more literal translations can sometimes display a different general pattern from free translations. In the present paper a distinction has been drawn between passive constructions that are ‘strict’ translations, in which either the Old English and the Latin correspond in every respect or else only minor changes such as a change of tense or mood have taken place, and those which are ‘free’ translations, in which the Old English construction translates an active Latin verb or a different syntactic category such as a noun, or does not correspond directly to any Latin form.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An additional way in which translation can influence the form of texts was suggested by Macleod (: 333–6), which found that more literal translations can sometimes display a different general pattern from free translations. In the present paper a distinction has been drawn between passive constructions that are ‘strict’ translations, in which either the Old English and the Latin correspond in every respect or else only minor changes such as a change of tense or mood have taken place, and those which are ‘free’ translations, in which the Old English construction translates an active Latin verb or a different syntactic category such as a noun, or does not correspond directly to any Latin form.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the amount of manual analysis required, only a subset of the Corpus was analysed; it will be seen that this was still sufficient to provide significant results. A starting point for the sampling methods was the corpus used in Macleod (), a methodologically similar study; however, alterations have been made to this schema where appropriate, as we explain below. Texts were chosen to represent a mix of different time periods and stylistic diversity.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations